Islamic constitutions and religious minorities - Moamen Gouda; Jerg Gutmann (University of Hamburg, Institute of Law and Economics (ILE), 2018)
This study examines the effect of formal institutions, specifically constitutional provi-sions, on minority discrimination in Muslim societies. We hypothesize that those Muslim countries in which (political) Islam constitutes an important constraint in the legislative process experience more discrimination against minorities than other (Muslim) coun-tries. In other words, as Islam becomes a constitutionally prescribed source of legisla-tion in Muslim societies, it is expected that subsequent laws will be more likely in viola-tion of basic rights of minorities. In our empirical analysis, we find that where the su-premacy of Islam and Shari'a is constitutionally entrenched, religious minorities are in-deed likely to face more discrimination. Instrumental variable regressions support our interpretation that this result reflects a causal effect of constitutional rules on social out-comes. We find no evidence that Islam encourages minority discrimination if it is not constitutionalized. Our results confirm the grave dangers entailed in the institutionaliza-tion of supreme values.
Keywords: J15; K38; Z12; Z18; 340; minority rights; discrimination; constitutions; Islam; Islamic constitutionalism